What is associated with reported acute respiratory infection in children under 5 and PCV vaccination in children aged 1-36 months in Malawi? A secondary data analysis using the Malawi 2014 MICS survey. - Justine Gosling; Tim Colbourn (PLoS ONE)
Introduction Acute respiratory illness (ARI) is a leading cause of mortality in children under 5 (CU5) in Malawi and can be prevented with 3-dose pneumococcal conjugate vaccine (PCV). There has been no national study in Malawi that seeks to associate social economic factors leading to PCV vaccine uptake and reported acute respiratory infections (RARI). The objectives of our study were to do this. Methods We conducted a cross-sectional analysis of secondary data from the 2014 UNICEF Malawi Multiple Indicator Cluster Survey to construct mutlivariable logistic regression models for independent associations with PCV 1/2/3 immunisation and RARI. Results 56% of CU5 in Malawi RARI in the 2 week recall period of the survey. Independent associations with reduced odds of RARI were central region living (OR 0.82, 95%CI (0.71-0.93)) middle (OR 0.84, (0.73-0.97)) fourth (OR 0.79, (0.68-0.92)) and richest wealth quintiles (OR 0.73, (0.60-0.88)). Using straw/shrubs for fuel was associated with increased RARI (OR 3.13, (1.00-9.79)). Among 1-36 month olds, in 2014, 93.3% received PCV1, 86.8% PCV2 and 77.0% PCV3. Between 2011-2014, the average age in months for a child to receive PCV1/2/3 reduced by 26.6 for PCV1, 26.4 for PCV2, and 26.1 for PCV 3. Independent predicators for increased odds of all 3 PCV doses, relative to 0-5 age group, were age group 6-11 (OR 21.8, (18.2-26.1) 12-23 (OR 27.5, (23.5-32.2) 24-36 months (OR 9.09, (7.89-10.5), mothers having a secondary (OR 1.52, (1.25-1.84)) or higher education (OR 2.68, (1.43-5.04) when compared to no education, and children in the middle (OR 1.24, (1.07-1.43)) fourth (OR 1.27, (1.09-1.48)) richest (OR 1.54, (1.27-1.88)) wealth quintiles relative to the lowest. Children living with 4-6 other children was independently associated with reduced odds of receiving all 3 PCV doses (OR 0.56, (0.33-0.96). Conclusion We report nationally representative social economic associations with RARI and PCV vaccine uptake and coverage estimates. We found reductions in the average age a child receives all 3 PCV vaccine doses between 2011-2014.